Internet of things (IoT): Evolution, components and applications fields - Gunduz, Muhammed Zekeriya; Das, Resul (Pamukkale Univ, 2018)
This study addresses the Internet of Things. Main enabling factor of this promising paradigm is the integration of several technologies and communication solutions. Identification and tracking technologies, wired and wireless sensors and actuator networks, enhanced communication protocols, and distributed intelligence for smart objects are just the most relevant. As one can easily imagine, any serious contribution to the advance of the Internet of Things must necessarily be the result of synergetic activities conducted in different fields of knowledge, such as telecommunications, informatics, electronics and social science. In this context, in the study IoT's basic concepts, components, basic security rules and the systems which enabling IoT's evolution were examined.
Keywords: Internet of things (IoT); Applications of IoT; Internet of everything (IoE); Big data; Security of IoT